Reliability and validity of a computer-based knowledge mapping system to measure content understanding. - Herl, H. E.; O'Neil, H. F.; Chung, G. K. W. K. (Computers in Human Behavior)
Part of a special issue on computer-based performance assessment of problem solving. Findings from two different administrations of computer-based knowledge mapping systems developed by the National Center for Research on Evaluation, Standards, and Student Testing (CRESST) are discussed; and important feasibility, reliability, and validity issues relative to a model-based approach to knowledge mapping are considered. The mapping studies in which middle and high school students participated involved the construction of group maps while collaborating over a network and the construction of individual maps and attempts to improve the maps while searching a Web space. it was observed that knowledge map scores increased significantly from fall to spring for students involved in the second mapping study. This supports the position that students' abilities in processing and searching for information on the Internet may have increased as a result of using computer technology during the school year. No clear relationships were observed among content understanding and collaboration.